The Philanthropist in Neo-Victorian Literature: (Im)Proper Femininity, Gender Inversion and Freakishness - Pettersson, Lin Elinor (Universidad de La Laguna, 2017)
The present article singles out the female philanthropist in neo-Victorian fiction to explore the patriarchal unease regarding the unsexing effect of feminism in the mid-Victorian era as well as the literary constructions and contestations of the concept of gender inversion. I will examine how social anxiety regarding feminists materialises through repeated attempts of locating physical traces of gender inversion on the body both then and now. First, I will analyse Michel Faber’s use of Victorian sensationalist perspectives on the New Woman through the lens of freakery in The Crimson Petal and the White (2002). Then I will explore how Emma Donoghue challenges dominant constructions of masculinity and femininity to support lesbian advocacy in The Sealed Letter (2008).
Keywords: Feminismo; Lesbian; Michel Faber; Emma Donoghue; Neo-Victorianism; Female philanthropy; Gender inversion; Freak; Female masculinity